GEOMETRIC EXPLORATION IN TORAJA CARVING - Beatric Videlia Remme'; Yusem Ba'ru (MATEMATIKA DAN PEMBELAJARAN, 2020)
Toraja carving is rich in mathematical concepts, especially geometric concepts, this is because in Toraja carving there are many geometric concepts such as squares, rectangles, triangles, and so on. This fact shows that the concepts of mathematics, especially geometry have been used by our ancestors since ancient times. The concept of geometry combined with Toraja local wisdom is expected to be able to facilitate learning geometry both in class and in college. Besides, it can be a means of preserving Toraja culture, especially for the younger generation of Toraja. The purpose of this research is to examine what geometric concepts are contained in Toraja carvings, as well as the meaning contained in them. This research was conducted in 3 (three) stages. Data were obtained using observation and interviews with 5 informants, namely those who understand the ins and outs of Toraja culture. From the research results, it is found that in Toraja carving, there are geometric concepts such as diagonals, parallel lines, symmetry, curved lines, squares, rectangles, trapezoid. Each carving has its own meaning and matches the name of each carving. The symbolic meaning in Torajan carvings generally describes the life of the Toraja people in relation to God, others, and their surroundings.